Quality as Subjectively Measured Value - P. S. Serenkov; V. M. Romanchak (Приборы и методы измерений)
The paper identifies the problem of ensuring the reliability of measurement results of quality characteristics as subjective values and their correct application in logical and mathematical models of making decisions. The purpose of this study is to increase the reliability of expert evaluation of individual characteristics of the quality of processes, products, systems.The article describes basic methodological approaches to subjective measurements represented by the classical, operational and representational theories of measurement. The most acceptable for the purposes of ensuring the reliability of the expert evaluation of the single quality characteristics a representative theory, suggesting that the subjective value can be measured only in nominal or ordinal scales was determined. The contradiction is established: the possibility of measuring of single quality characteristics in the ordinal scale does not meet the needs of specialists in the field of quality, whouse subjective measurements to solve problems of analysis and decision-making, requiring the use of logical and mathematical models; in that way estimates should be expressed at least in the interval scale. The article substantiates the best solution of this problem by use of the rating scale which has properties of both ordinal and interval scales.Within the framework of the expert methods of quality measurements development two fundamental elements of the methodology of subjective measurements of subjective values from the standpoint of representative theory are formulated: 1) the rating scale as a modified scale of ranks, 2) the method of organization of the measurement process as a method of alternative assessment of expert preferences.Much attention is given to axiomatic of the rating scale having properties of both ordinal and interval scales. The algorithm of implementation of alternative assessment's of expert preferences method which is based on a special two-stage plan of alternative expert survey and statistical criterion of preferences' stability was suggested. In conjunction, the methodologies of subjective measurements of subjective values ensure the correctness of the rating scale's formation and conversion of the values of quality characteristics in the form of ratings in the corresponding values expressed at least in the scale of intervals.